Guide Museum of Contemporary Art - Kaitavuori, Kaija; KIASMA (Museum of Contemporary Art), Helsinki (Helsinki : Museum of Contemporary Art, 1993)
Mäkelä, Marika ; Nevalainen, Pekka ; Ruutsalo, Eino ; Kajander, Ismo ; Rantanen, Ulla ; Kolar, Jiri ; Fabre, Jan ; Jankola, Alpo ; Kaivanto, Kimmo ; Liulia, Marita ; Andersson, Jan-Erik ; Tapiola, Marjatta ; etc.
boek